Sosialisasi dan Inovasi Kewirausahaan dalam Upaya Peningkatan Daya Saing UMKM di Desa Sindu Wati Kecamatan Sidemen Kabupaten Karangasem Provinsi Bali - Riduwan Riduwan (Jurnal Pengabdian Masyarakat, 2025)
The assistance program, socialization, and innovation for MSMEs in Sinduwati Village, Sidemen District, Karangasem Regency, Bali, aims to enhance the competitiveness of MSMEs through socialization and support related to innovation and business digitalization. The methods used include training, workshops, and direct consultations with MSME actors regarding innovative strategies, the utilization of digital technology, and the optimization of social media and e-commerce platforms. The results of this activity show that participants have experienced an increase in understanding and skills in implementing business digitalization, enabling them to expand their market reach and improve their operational efficiency. With this socialization, it is hoped that MSMEs can be more adaptive to technological developments and be able to compete in the digital economy era. Evaluations are conducted periodically to ensure the sustainability of the program and adaptation to the dynamic needs of business actors. This program has proven to be effective in strengthening the digital capabilities of local MSMEs and supporting economic growth based on regional potential as well as promoting sustainability.